Nutritional characteristics of afro-descendant schoolchildren of Colombian pacific southwest coast - Ortega B,Rubén Andrés (Sociedad Chilena de Nutrición, Bromatología y Toxicología, 2016)
This paper provides a current diagnosis on the nutritional status of schoolchildren of pacific coast of Cauca in Colombia. A secondary analysis of publicly available anthropometric data was performed. BMI/Age and H/Age indices, nutritional classification and their association with gender, ethnicity, age and geographical area of 6793 students aged 5 to 18 years of the municipalities of Guapi, Lopez de Micay and Timbiquí were determined. Normality was the prevalent nutritional status in the three municipalities for schoolchildren of all ages according to BMI and height (65.7% and 59.3 %, respectively); Guapi was found to be the main contributor. There was no significant differences of BMI and region among males and females. Adolescents between 12 and 14 years old had percentages of stunting significantly higher than other age ranges. Results highlight the need to identify, measure and monitor indicators of health, food habits and sociodemographic aspects of schoolchildren in this region to strictly explore whether Colombian black children fit WHO patterns and to provide specific information for successful national nutrition policy planning for this population.